Variations in State Sex Offender Statutes: Implications for U.S. Higher Education - Custer, Bradley D. (Criminal justice policy review, 2019)
State sex offender statutes have been shown to vary widely in the United States. The rules found in some state statutes targeting registered sex offenders who are students or employees at higher education institutions have never been studied. I analyzed sex offender statutes and public sex offender registry websites from all U.S. states and territories and found 10 unique rules across 20 states for sex offenders in higher education. In addition, the websites of 31 states and territories listed the name or address of the institution where a registrant attends or works, and nine websites allow users to search for registrants by institution. Although research suggests higher education may be an effective rehabilitation strategy for sex offenders, some of these policies may be barriers to pursuing a college degree. I offer recommendations for reducing barriers to higher education through policymaking and for conducting future policy evaluations.